Siberian Robinsons - Kopeć, Zbigniew (Porównania, 2019)
The paper examines the protagonists of the Polish prose written in the 20th century and at the close of the 19th century: the novel Anima Vilis by Maria Rodziewiczówna, two texts by Wacław Sieroszewski: the novel Na kresach lasów (At the Edge of the Woods) and the short story W matni (In a Snare) as well as the novel by Igor Newerly Wzgórze błękitnego snu (The Hill of the Blue Dream). They are connected by the fact that their plot takes place in Siberia, and, additionally, plenty of opportunity opens up for their protagonists. Siberia is depicted in a way that is distant from the presentations showing it “as the biggest prison in the world” or hell to which Poles are deported. It is described as the land of great opportunity, open for everybody who wants and can work. The main characters are not exiles—presented in a martyrologic and Romantic manner—but active, hard-working people. The characters from the novels by Rodziewiczówna and Newerly have a lot in common with the main hero of The Life and Strange Surprizing Adventures of Robinson Crusoe, in contrast to the protagonists by Sieroszewski from the above-mentioned works, who, when they found themselves on “the desert island”, which is the Yakut village lost in the taiga, do not perform the roles typical of Robinson. Important for the problems discussed in my paper is the second volume of Defoe’s novel: The Farther Adventures of Robinson Crusoe, where Siberia is portrayed as being colonized by Russians. In this process of colonization, willingly or not, also participate other protagonists of the texts discussed in this paper.